Uveitis characteristics and multiple sclerosis phenotype of patients with multiple sclerosis-associated uveitis (2024)
Purpose: To summarize and meta-analyze uveitis characteristics and multiple sclerosis (MS) phenotype of patients with multiple sclerosis-associated uveitis (MSAU) within a systematic review and meta-analysis. Methods: A comprehensive literature search was performed on January 25, 2023, utilizing PubMed, Embase, and Virtual Health Library (VHL) databases. We included studies involving patients with MSAU, such as case series with over 10 patients, cross-sectional, case-control, and cohort studies. Quality and risk of bias were assessed using CLARITY tools and validated metrics like the Hoy et al. and Hassan Murad et al. tools. The pooled analysis focused on 1) uveitis characteristics, 2) ocular complications, 3) MS phenotype, and 3) administered treatments for uveitis and MS. Gender-based subgroup analysis was conducted across continents